Review of Heat Effect for wood Properties - Bouaphavong, Douangta (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study aimed to analyse the effect of physical and mechanical properties of thermally wood. The study compiled information from review of literature that related to the thermo wood. One-way and two factors ANOVA table were used to analyses data. The result showed that thermo wood property was affected based on physical and mechanical. Physical property effective was density decreasing but improved biological durability. Mechanical property like hardness was increasing, but tension, MOR, compression was decreasing and MOE was not change.